Size dependent electronic structure of LiFePO4 probed using X-ray absorption and Mössbauer spectroscopy. Issue 16 (12th April 2022) - Ali, Mahboob; Tsud, Nataliya; Meena, Sher Singh; Murugavel, Sevi
Abstract : We present the combined Mössbauer and X-ray absorption spectroscopy investigation of the electronic structure and local site symmetry of Fe in olivine structured LiFePO4 (LFP) with crystallite size (CS). Abstract : We present the combined Mössbauer and X-ray absorption spectroscopy investigation of the electronic structure and local site symmetry of Fe in olivine structured LiFePO4 (LFP) with crystallite size (CS). The lattice parameters are found to contract with a decrease in CS, monotonously, whereas the electronic structural parameters exhibit two different regions with a threshold anomaly of around ≈30 nm. 57 Fe Mössbauer studies reveal the coexistence of Fe 2+ and Fe 3+ sites and their relative concentrations are mainly determined by CS, which provides a comprehensive insight into the electronic structure of LFP at the mesoscopic level. The soft X-ray absorption unequivocally unravels the valence states of Fe 3d electrons in proximity to the Fermi level, which are prone to the local lattice distortion. The obtained spectra fingerprint the effect of CS supplying rich information on valency, lithium-ion vacancy concentration, covalency and crystal field. By comparing the spectra with the results of charge-transfer multiplet calculations, which include the full-atomic multiplet theory, we have found that the local symmetry of Fe ions is well described by the D 4h point group with intermixing between eg and t2g orbitals. The unique structural and electronic properties of LFP are closely interlinked with changes in the bonding character, which shows the strong dependency on CS. The evolution of 3d states is in overall agreement with the local lattice distortion and provides the origin of the size effects on the electronic structure of olivine phosphate and other transition metal ion-containing materials.